A ratiometric fluorometric probe for doxycycline in food by using bovine serum albumin protected Au nanoclusters. (November 2021) - Chen, Yinyin; Wang, Xini; Lu, Changfang; Wu, Wei; Wang, Xianxiang
Abstract: Doxycycline (DOX) is widely used as feed additive and may remain in animal food. Thus, the detection of DOX in food field has become important. This work has reported a simple and rapid strategy to detect DOX by ratiometric fluorescence method without any sensitization materials based on bovine serum albumin (BSA) protected Au nanoclusters (BSA-Au NCs). Under excitation at 390 nm, the BSA-Au NCs has displayed two distinct emission peaks at 510 nm and 640 nm which are respectively originated from BSA and Au NCs, respectively. The fluorescence intensity ratio of I 510 / I 640 of BSA-Au NCs probe has presented a good linear range (0.1–30 μM) and 0.006 μM limit of detection for DOX. This method was used successfully to detect DOX in food samples and the good recoveries reached 96.7–103.7%. The research has showed that potential application of BSA-Au NCs in food field because of its convenient synthesis scheme and excellent selectivity and sensitivity. Highlights: A ratiometric fluorometric probe for doxycycline was developed. BSA-Au NCs has displayed two distinct fluorescence emission peaks at 510 nm and 640 nm. The method has good selectivity and sensitivity for doxycycline.